HUBUNGAN DUKUNGAN KELUARGA DENGAN PEMBERIAN ASI EKSKLUSIF PADA BAYI DI PUSKESMAS RANOTANA WERU - Mamangkey, Suharti J.F; Rompas, Sefti; Masi, Gresty (JURNAL KEPERAWATAN, 2018)
Abstract : Breast Milk is the best food for babies, because the content of very special and perfectits nutrition value, as well as in accoordance with the needs of the growing baby flower. Duringbreast feeding mothers need support one family support. During breast feeding mothers needsupport on a family support. Familly support is a major external factors affect the success ofExclusive breast milk. The Purpose of the research is known to support the family relationshipwith exclusive breast feeding on infants in Clinic Ranotana Weru. Design Research isdescriptive research of correlative with the approach of Cross Sectional. Samples in thisresearch is the mother who has a baby aged 6-12 months as much as 103 respondents in themethod of is simple random sampling. The Result of the Research using statistical test of Chi-Square with a confidence level of 95% (Î±=0,05%) obtained value p=0,000 < (Î±) 0,05%.Research Findings of this study showed that there is a significant relationship between familysupport with exclusive breast feeding on infants in Clinic Ranotana Weru.Keywords : Family support, Exclusive breast milkAbstrak : Air Susu Ibu (ASI) adalah makanan terbaik untuk bayi, karena kandungan gizinyasangat khusus dan sempurna serta sesuai dengan kebutuhan tumbuh kembang bayi. Selama Ibumenyusui ibu membutuhkan dukungan salah satunya dukungan keluarga. Dukungan keluargamerupakan faktor eksternal yang paling besar pengaruhnya terhadap keberhasilan ASIEksklusif. Tujuan Penelitian diketahui hubungan dukungan keluarga dengan pemberian asieksklusif pada bayi di Puskesmas Ranotana Weru. Desain Penelitian merupakan penelitiandeskriptif korelatif dengan pendekatan cross sectional. Sampel pada penelitian ini adalah ibuyang mempunyai bayi berusia 6-12 bulan sebanyak 103 responden secara metode simplerandom sampling. Hasil Penelitian menggunakan uji statistik Chi-Square dengan tingkatkepercayaan 95% (Î±=0,05%), didapatkan nilai p-value=0,000 < (Î±) 0,05%. Simpulan hasilpenelitian ini menunjukkan bahwa ada hubungan yang signifikan antara dukungan keluargadengan pemberian ASI eksklusif pada bayi di Puskesmas Ranotana Weru.Kata Kunci : Dukungan keluarga, Asi eksklusif